Upaya Deteksi Dini Risiko Tinggi Kehamilan Ditentukan Oleh Pengetahuan Dan Pemeriksaan Kehamilan Di Pulau Osi - Arindiah Puspo Windari; Sri Ayu Lohy (Jurnal Pengabmas Masyarakat Sehat, 2019)
The most common cause of maternal death is bleeding (30.3%), followed by hypertension in pregnancy (27.1%), infection (7%). Other causes, 45%, are quite large, including non-obstetric causes. High maternal mortality is also caused by the high number of unexpected pregnancies. Approximately 65% of pregnancies still occur because "4 too" associated with pregnancies "too young (less than 20 years)," too old: (more than 35 years), "too often (pregnancy interval less than 2 years," too many”(more than 3 children). Most maternal deaths can be prevented if adequate treatment is provided in health care facilities. Time and transportation factors are very decisive in referring to high-risk cases. Therefore, detection of risk factors in mothers is good by personnel. Health and society is one of the important efforts in preventing death and morbidity. To avoid the risk of complications in pregnancy and childbirth, every pregnant woman needs at least 4 antenatal care, namely once in the first trimester (0-12 weeks gestation), one times in the second trimester (12-24 weeks of gestation), and twice in the second trimester third steer (24 weeks gestation until delivery). Keywords: Early Detection Of High Risk Pregnancy, Pregnancy Test.